ANALISIS DETERMINAN PENGELUARAN KONSUMSI MAKRO RUMAH TANGGA DI INDONESIA - Puspi Eko Wiranthi (Faculty of Economic and Business Syarif Hidayatullah State Islamic University of Jakarta, 2014)
Domination allocation of Gross Domestic Product by its use in household consumption expenditure showed the importance of this type of expenditure to national economic growth and the household welfare. Under these conditions, this study aims to analyze the development of household consumption expenditure in Indonesia during the period 2000 to 2014 and the factors that influence the household consumption expenditure. By using multiple linear regressions, the study finds that the factors of national income, interest rates and fuel prices significantly affect national household consumption expenditure. To further boost economic growth and welfare, the government should imply appropriate policies by increasing household incomes through the expansion of employment opportunities, as well as maintaining the stability of interest rates and minimizing the negative impacts of the rising of oil prices.DOI:10.15408/sjie.v3i2.2063